2020
DOI: 10.1016/j.ajhg.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Hi-C Identifies Complex Genomic Rearrangements and TAD-Shuffling in Developmental Diseases

Abstract: Genome-wide analysis methods, such as array comparative genomic hybridization (CGH) and whole-genome sequencing (WGS), have greatly advanced the identification of structural variants (SVs) in the human genome. However, even with standard high-throughput sequencing techniques, complex rearrangements with multiple breakpoints are often difficult to resolve, and predicting their effects on gene expression and phenotype remains a challenge. Here, we address these problems by using high-throughput chromosome confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 47 publications
2
92
0
3
Order By: Relevance
“…This dependence of chromatin contacts on genomic distance has been observed in all studied cell types [3][4][5] and can be utilized to infer the order of scaffolds in poorly assembled genomes, providing chromosome-length assemblies [6][7][8][9][10][11]. For species with a well-assembled genome, such as humans, the Hi-C technique can be used to detect structural variations, which alter the order of genomic segments and therefore lead to significant changes in chromatin interaction frequencies [6,[12][13][14][15][16][17]. In addition, one can extract information about single nucleotide variations (SNVs) from Hi-C reads.…”
Section: Introductionmentioning
confidence: 86%
“…This dependence of chromatin contacts on genomic distance has been observed in all studied cell types [3][4][5] and can be utilized to infer the order of scaffolds in poorly assembled genomes, providing chromosome-length assemblies [6][7][8][9][10][11]. For species with a well-assembled genome, such as humans, the Hi-C technique can be used to detect structural variations, which alter the order of genomic segments and therefore lead to significant changes in chromatin interaction frequencies [6,[12][13][14][15][16][17]. In addition, one can extract information about single nucleotide variations (SNVs) from Hi-C reads.…”
Section: Introductionmentioning
confidence: 86%
“…An enhancer and its cognate target gene almost always reside within a TAD; i.e., an enhancer’s functional jurisdiction is largely limited to the home TAD as it seldom contacts genes residing in neighboring TADs [ 232 , 233 ]. Sequence alterations at the TAD boundaries can restructure the adjacent TADs such that an enhancer can contact and activate a gene that resides in an otherwise inaccessible TAD, best illustrated in developmental disorders [ 234 , 235 ]. This spatial restriction eases the effort for the enhancer and cognate genes to find each other.…”
Section: Mechanism Of Enhancer Actionmentioning
confidence: 99%
“…The deletion removes at least nine enhancer elements driving expression in the central nervous system (CNS). Recently, Melo et al identified a translocation disrupting the CTNNA2 TAD in a patient with ID and DD 116 . Although homozygous variants in this gene cause cortical dysplasia and other brain malformations, a noncoding disease mechanism has not yet been investigated.…”
Section: Disruption Of Near Cis-regulatory Elements (Promoter 5' and 3mentioning
confidence: 99%